Extension of the Freiberg Layer Model by Means of Solidification for Roll Casting. Issue 8 (12th February 2022) - Weiner, Max; Schmidtchen, Matthias; Prahl, Ulrich
Abstract : Finite element method (FEM) simulations offer deep and detailed modeling of complex processes, but with a high effort of computation power and time. For the special purpose of flat rolling, a layer model is developed by Schmidtchen earlier based on the classic elementary theory of plasticity with the purpose to model inhomogeneous behavior with a significant lower effort at computation. In a previous work, this model was extended with elastic–plastic material behavior. Herein, the model is extended by a viscose zone at the entry for the modeling of roll casting. It is now possible to model the inhomogeneous solidification of a melt in the roll gap and proceed with elastic–plastic inhomogeneous flat rolling in the solid region. The results are compared with FEM simulations from the literature and found to fit well together. But, the current model offers more plausible stress curves in the solid region, because an elastic–plastic material model is applied, where common FEM simulations are only able to work with viscose material laws in the whole roll gap. Abstract : A layer model based on slab method of horizontal strip roll casting is built and tested. The new model has the benefit of working with two different material laws, viscose and elastic–plastic, which was not possible with finite element models (FEMs) before. It is tested against FEM models and let to comparable results regarding point of full solidification and exit temperatures.